Persepsi Kepuasan Kerja di Perguran Tinggi - Yayuk Chayatun Machsunah; Ratna Nurdiana (Journal of Education and Religious Studies, 2022)
This study aims to determine how much influence employee job satisfaction at PGRI Adi Buana University (UNIPA) Surabaya PSDKU Lamongan has. Job satisfaction is an individual's emotional state that can be expressed in feelings of happiness and positive emotions and this comes from an assessment of a job or work experience which can later affect performance performance, either directly or indirectly. This research is descriptive. The population and samples used were employees at UNIPA Surabaya PSDKU Lamongan, from BAAK (Bureau of Academic and Student Administration), and BAUK (Bureau of General Administration and Finance). The results of this study indicate that employee job satisfaction is not only about the salary received but there are several factors that influence it